2005
DOI: 10.1136/adc.2005.079608
|View full text |Cite
|
Sign up to set email alerts
|

Plethysmograph and interrupter resistance measurements in prematurely born young children

Abstract: Background: Airways obstruction in premature infants is often assessed by plethysmography, which requires sedation. The interrupter (Rint) technique does not require sedation, but has rarely been examined in children under 2 years of age. Objective: To compare Rint results with plethysmographic measurements of airway resistance (Raw) in prematurely born, young children. Design: Prospective study. Setting: Infant and Paediatric Lung Function Laboratories. Patients: Thirty children with a median gestational age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(34 reference statements)
0
5
2
Order By: Relevance
“…Diverging results might be due to differences in study age, data acquisition, and analysis software, occlusion time, and quality control. In another study, Rint measured during peak inspiratory flow in sedated preterm infants at 1 year was lower than in our study. Previous methodological work compared Rint measurements completed during inspiration and expiration in preschool children, and reported a higher Rint during expiration .…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Diverging results might be due to differences in study age, data acquisition, and analysis software, occlusion time, and quality control. In another study, Rint measured during peak inspiratory flow in sedated preterm infants at 1 year was lower than in our study. Previous methodological work compared Rint measurements completed during inspiration and expiration in preschool children, and reported a higher Rint during expiration .…”
Section: Discussioncontrasting
confidence: 83%
“…Previous methodological work compared Rint measurements completed during inspiration and expiration in preschool children, and reported a higher Rint during expiration. 7,26 This methodological impact on Rint values may be one reason for a higher Rint in our study compared to the study by Thomas et al 18 Several studies from children reported that Rint decreases with increasing age and height. 7,27,28 In regards to Rint measurements in infants, it is still unclear which factor is a more relevant predictor in this age group.…”
Section: Discriminative Power Of Rintcontrasting
confidence: 47%
See 2 more Smart Citations
“…The finding of relatively better pulmonary function in boys than girls was unexpected, as most previous studies have reported worse morbidity in male infants following preterm birth. 4 , 33 , 34 Given that investigation of sex differences was not an a priori hypothesis and the relatively small sample size once subsets were examined according to ethnic group, gestational age sex and sex, this finding needs to be interpreted with caution, as it may simply reflect a chance finding due to sampling. In addition, these findings may be biased by the fact that a larger proportion of SGA infants were recruited to the PTC than EP group (possibly reflecting the fact that such children rarely survive if born EP) and that of these children, twice as many were girls.…”
Section: Discussionmentioning
confidence: 99%